BENEFITS AND RISKS OF PACIFIER USE - A NARRATIVE REVIEW ON THE MEDICAL IMPACT OF PACIFIER USE DURING INFANCY AND EARLY CHILDHOOD - Monika Ucieklak; Patrycja Ucieklak; Jarosław Ucieklak; Dawid Musialik; Karol Poplicha; Konrad Poplicha; Piotr Sobkiewicz; Martyna Grodzińska; Aleksandra Piech; Karolina Pasierb (International Journal of Innovative Technologies in Social Science, 2025)
Background: Pacifier use remains a common practice during infancy and early childhood worldwide that has both benefits and risks. Its use has become highly prevalent in recent years and is sometimes considered overused, as it provides an easy and convenient method for calming and soothing children. Objective: This review aims to summarize current scientific evidence regarding pacifier use focusing on both positive and negative outcomes to provide an overview that may help with the establishment of the clinical recommendations. Methods: A narrative review of different randomized controlled trials and cohort studies investigating the positive and negative impacts of pacifier use such as SIDS risk, pain management, otitis media, dental malocclusions and breast-feeding. Results: The reviewed studies indicate that pacifier use reduces risk of sudden infant death syndrome (SIDS) and is an effective way of pain management during minor medical procedures. However, evidence shows an association between pacifier use and increased incidence of acute otitis media, dental malocclusions in cases of prolonged use and negative impact on breastfeeding when introduced before lactation is well established. Conclusion: The evidence supports selective use of pacifier, particularly during the first year of life with its introduction delayed until breastfeeding is well established, which happens usually around 1 month of age. Its use should be limited mainly to sleep periods and gradually limited by 12 months of age. Proper timing and restricted duration are key to maximising benefits while reducing risks.